2020
DOI: 10.1182/bloodadvances.2020003170
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with hematologic malignancies and COVID-19: a report from the ASH Research Collaborative Data Hub

Abstract: Coronavirus disease 2019 (COVID-19) is an illness resulting from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that emerged in late 2019. Patients with cancer, and especially those with hematologic malignancies, may be at especially high risk of adverse outcomes, including mortality resulting from COVID-19 infection. The ASH Research Collaborative COVID-19 Registry for Hematology was developed to study features and outcomes of COVID-19 infection in patients with underlying blood disorders, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(153 citation statements)
references
References 23 publications
8
143
1
1
Order By: Relevance
“…Although the diagnosis of leukemia, in the aforementioned studies, was performed earlier than our case, the prognosis of patients was also poor. This is in accordance with recent multicenter studies reporting that cancer patients have been affected by COVID-19 during the pandemic in a rather similar incidence to the general population; however, the outcome of SARS-CoV-2 infection is significantly worse in patients with hematologic malignancies [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Although the diagnosis of leukemia, in the aforementioned studies, was performed earlier than our case, the prognosis of patients was also poor. This is in accordance with recent multicenter studies reporting that cancer patients have been affected by COVID-19 during the pandemic in a rather similar incidence to the general population; however, the outcome of SARS-CoV-2 infection is significantly worse in patients with hematologic malignancies [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Tumors and antitumoral therapy potentially compromise the immune system thus influencing the disease severity and prognosis. It has been reported that hematological malignancies have higher mortality for COVID-19 than general population [ 2 ]. A decrease in the innate antiviral response and chronic lymphopenia are common in neoplastic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Early reports about COVID-19 indicated substantially higher morbidity and mortality in HCT recipients than in the general population ( 1 , 2 , 3 , 4 , 5 , 6 ). Thirty-day mortality rates of 22-32% were seen ( 1 , 2 ).…”
Section: Covid-19: a Huge Disruptormentioning
confidence: 99%
“…Four categories of indirect factors on the centers that might affect center-specific performance were also identified: ( 1 ) COVID-19 burden; ( 2 ) locality of the center and patient; ( 3 ) impact of COVID-19 on center survival; ( 4 ) indirect effects of COVID-19 burden on a center's practices. COVID-19 Burden.…”
Section: The Cibmtr's Responsementioning
confidence: 99%